Examining the contribution of an underutilized food source, Bambara Groundnut, in improving protein intake in Sub-Saharan Africa - Veldsman, Zani; Pretorius, Beulah; Schönfeldt, Hettie Carina (Frontiers in Sustainable Food Systems, 2023)
Bambara groundnut (BGN) is an indigenous, underutilised crop renowned for its climate resilience in Sub-Saharan Africa (SSA). However, there is a dearth of research on the nutritional contributions of this crop to the diet. This study aims to investigate the nutritional profile and protein quality of BGN, focusing on its potential to enhance dietary diversity and improve the nutritional quality of diets in SSA countries. A comprehensive nutritional analysis was conducted, encompassing proximate analysis, dietary fibre, total fat, minerals, fatty acid, and amino acid profiles of BGN samples obtained from three distinct regions in the Mpumalanga (MP) province of South Africa (SA). Furthermore, the protein quality was assessed using CSEAA, IEAA, PDCAAS, and DIAAS methodologies, enabling a comparison with other commonly consumed pulses and legumes in the region. Results indicate that dehulled and cooked BGN contains approximately 18.9% carbohydrates, 9.4% protein, and 3% fat. Thus, BGN holds promise as a valuable complementary protein source within traditional diets of the region. Furthermore, combining BGN with commonly consumed plant-based foods, such as maize and soybeans, has the potential to enhance protein quality and dietary diversity, thereby improving the overall nutritional adequacy of diets.